A hístória e epistemologia da ciência no ensino da química na educação básica em vista à sua aprendizagem significativa - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The History and Epistemology of Science has influenced several discussions in the last decades in the context of Teaching Chemistry, considering its potential contribution to the understanding of its concepts/principles. This paperbrings new elements thatcorroborate this reflection, when presenting and applying, together with a 2nd year High School class of a public school in the city of Lavras do Sul/RS, a didactic-pedagogical proposal based on texts available in textbooks that contemplate aspects related to the dynamic and socially constructed nature of Science. For that, it was used the pedagogical strategy of Conceptual Maps, supported by the theory of Significant Learning. As resources for data analysis, we made use of Qualitative Research and Textual DiscursiveAnalysis (TDA). Based on the obtained results, a broad potential of this theoretical approach to the planning and development of the teaching actions was seen, since a change of conception in Sciences of the target public, thus breaking with the perspective of a Teaching of Chemistry whose conception is driven by the accumulation/transmission of information.
Keywords: História da Ciência; Aprendizagem Significativa; Mapas Conceituais; Science Hostory; Significant Learning; Conceptual Maps; CNPQ::CIENCIAS EXATAS E DA TERRA